Aquifer Protective Capacity, Soil Corrosivity and Groundwater Potential Evaluation using Electrical Resistivity Method at Kwata-Zawan Area, Jos, Northcentral Nigeria - Fwangmun Dalaham; Eti-mbuk Akanbi; Shola Odewumi (Malaysian Journal of Science and Advanced Technology)
Geophysical investigation involving electrical resistivity method was carried out to investigate the groundwater potential in Kwata-Zawan area, Jos, North central, Nigeria. Twenty (20) Vertical Electrical Sounding (VES) stations were occupied using Schlumberger configuration with current electrode separation (AB) varying from 1.5 to 125 m. The VES data was iteratively inverted using WINRESIST version 1.0 software to produce resistivity sounding curves. The qualitative interpretation of the curves showed HK, HA, KH, AA, AKQ, QH, HHK, HKQ, AAK, H, KHK, AK, AKH, K, and A type curves. Kwata-Zawan area showed three (3) to five (5) geo-electric layers; top-soil, laterite, clay, fracture/weathered basement and fresh basement. From the longitudinal conductance values, the aquifer protective capacity rating from poor to moderate, implying that the ground water of the study area is susceptible to surface contaminants. Soil corrosivity results reveals that soils with practically non-corrosive, slightly corrosive and moderately corrosive tendencies occupy top soil of the study area; with soils that are practically non-corrosive occupying greater part. The groundwater potential of Kwata-Zawan area is characterized as poor, low and good aquifer potential zones. The good groundwater potential rating is found at VESs 4, 6, 15, 16, 17, 19 and 20.